2019
DOI: 10.1002/eji.201848037
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes alters immune response patterns to acute melioidosis in humans

Abstract: Diabetes mellitus (DM) is a serious global health problem currently affecting over 450 million people worldwide. Defining its interaction with major global infections is an international public health priority. Melioidosis is caused by Burkholderia pseudomallei, an exemplar pathogen for studying intracellular bacterial infection in the context of DM due to the 12‐fold increased risk in this group. We characterized immune correlates of survival in peripheral blood of acute melioidosis patients with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 63 publications
2
55
0
Order By: Relevance
“…To date, host immune responses by CD4 T cells in HIV-positive persons with melioidosis remain unknown. Host immune responses during acute melioidosis associated with survival have been shown to be dominated by CD8 T and NK cells (36,37), and some redundancy may occur to allow compensation of low CD4 counts in HIV.…”
Section: Discussionmentioning
confidence: 99%
“…To date, host immune responses by CD4 T cells in HIV-positive persons with melioidosis remain unknown. Host immune responses during acute melioidosis associated with survival have been shown to be dominated by CD8 T and NK cells (36,37), and some redundancy may occur to allow compensation of low CD4 counts in HIV.…”
Section: Discussionmentioning
confidence: 99%
“…However, Buddhisa et al have demonstrated that in patients with T2DM the expression of programmed cell death ligand 1 (PD-L1) on the surface of B. pseudomallei infected neutrophils is increased thus impairing T cell function ( 230 ). Kronsteiner et al, have demonstrated that CD3 + CD4 − CD8 − double-negative T cells and antibodies are important for the survival of diabetic melioidosis patients, while the survival of non-diabetics relies on CD8 + T cells and NK cells ( 231 ). They also indicated that IFN-γ release from γδ T-cells have an important role in the induction of protective immune responses in diabetic patients.…”
Section: Effects Of T2dm On the Susceptibility Of Patients To Infectimentioning
confidence: 99%
“…The essential role of IFN-γ in the early control of melioidosis has been indicated by murine in vitro and in vivo experiments as well as in clinical studies [ 41 ]. Blocking of IFN-γ in a melioidosis mouse model led to a drastically reduced LD50 and increased the bacterial burden in spleen and liver [ 42 ].…”
Section: Discussionmentioning
confidence: 99%